2020
DOI: 10.1186/s12981-020-00272-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of abacavir/lamivudine plus rilpivirine as a first-line regimen in treatment-naïve HIV-1 infected adults

Abstract: Background: The anti-retroviral combination of abacavir/lamivudine plus rilpivirine (ABC/3TC/RPV) is not recommended by international guidelines as the first-line regimen. However, it is potent, well-tolerated, and affordable, especially in resource-limited settings. This study evaluates the efficacy and safety of ABC/3TC/RPV as an initial regimen for treatment-naïve HIV-1 infected patients. Methods: A retrospective study was conducted in the largest HIV care centre in Singapore, with data collected June 2011 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 11 publications
(20 reference statements)
6
7
0
Order By: Relevance
“…AEs were observed amongst 31/222 patients (14.0%) and resolved either spontaneously or upon discontinuation of the medication. These results were comparable to the favourable results of SIMRIKI study, 10 as well as the local study on treatment-naïve HIV-infected patients, 14 which reported only 15.6% and 13.5% of patients with observed AEs respectively. The AE pro le seen in our study was also very similar to the local study which saw mostly neuropsychiatric AEs at a rate of 46.4% of all observed AEs compared to our study which saw 57.1% of observed AEs being neuropsychiatric.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…AEs were observed amongst 31/222 patients (14.0%) and resolved either spontaneously or upon discontinuation of the medication. These results were comparable to the favourable results of SIMRIKI study, 10 as well as the local study on treatment-naïve HIV-infected patients, 14 which reported only 15.6% and 13.5% of patients with observed AEs respectively. The AE pro le seen in our study was also very similar to the local study which saw mostly neuropsychiatric AEs at a rate of 46.4% of all observed AEs compared to our study which saw 57.1% of observed AEs being neuropsychiatric.…”
Section: Discussionsupporting
confidence: 87%
“…[11][12][13] The SIMRIKI study also saw 91.2% of their study population achieving the same outcome at 48 weeks. 10 A local study found that 96% of treatment naïve HIV-1 infected patients achieved virologic suppression at the end of 48 weeks of treatment with ABC/3TC + RPV, 14 which was comparable to that of our study in which 98.0% (197/201) of patients who completed follow-up without therapy discontinuation remained virologically suppressed. The ndings of our study reinforce existing primary literature that ABC/3TC + RPV can achieve effective, sustained virologic suppression.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations